2016
DOI: 10.1007/s00405-016-3950-4
|View full text |Cite
|
Sign up to set email alerts
|

Standardized pretreatment inflammatory laboratory markers and calculated ratios in patients with oral squamous cell carcinoma

Abstract: Analyzing the inflammatory microenvironment has become an important issue in the management of oral squamous cell carcinoma (OSCC). Pretreatment C-reactive protein (CRP) levels, leucocytes, monocytes, lymphocytes, neutrophils, basophils, eosinophils, platelets, neutrophil-to-lymphocyte ratio (NLR), derived NLR (dNLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) derived from the peripheral blood were analyzed. Receiver operating characteristic (ROC) curves determined a cut-off val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 85 publications
3
21
0
Order By: Relevance
“…Tumor, stromal, and immune cells in the tumor microenvironment secrete cytokines to facilitate the development and release of bone‐marrow neutrophils, and the resultant neutrophilia can be used as a diagnostic and prognostic biomarker for HNSCC. Neutrophil counts in the peripheral blood are elevated in patients with laryngeal and oral cancer and can differentiate cancers from benign lesions in the larynx and oral cavity . Increased neutrophil counts were demonstrated to be a prognostic marker in patients with head and neck cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor, stromal, and immune cells in the tumor microenvironment secrete cytokines to facilitate the development and release of bone‐marrow neutrophils, and the resultant neutrophilia can be used as a diagnostic and prognostic biomarker for HNSCC. Neutrophil counts in the peripheral blood are elevated in patients with laryngeal and oral cancer and can differentiate cancers from benign lesions in the larynx and oral cavity . Increased neutrophil counts were demonstrated to be a prognostic marker in patients with head and neck cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil counts in the peripheral blood are elevated in patients with laryngeal and oral cancer and can differentiate cancers from benign lesions in the larynx and oral cavity. [40][41][42] Increased neutrophil counts were demonstrated to be a prognostic marker in patients with head and neck cancer. 43 The prognostic capability of an increase in neutrophils in blood is further enhanced when the neutrophil count is shown as pretreatment NLR.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%
“…10 Previous studies have demonstrated the utility of numerous blood markers as prognostic factors for HNSCC, including serum squamous cell carcinoma (SCC) antigen, 11 C-reactive protein, 12 serum transaminase, 13 and hematologic markers. Tissue specimens allow for the direct examination of tumor and stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, blood markers are not affected by any heterogeneity within the tumor. 10 Previous studies have demonstrated the utility of numerous blood markers as prognostic factors for HNSCC, including serum squamous cell carcinoma (SCC) antigen, 11 C-reactive protein, 12 serum transaminase, 13 and hematologic markers. 14 Platelet count and plateletlymphocyte ratio (PLR) are hematologic makers that have shown prognostic abilities across many types of cancers.…”
Section: Introductionmentioning
confidence: 99%